1992
DOI: 10.1136/gut.33.11.1462
|View full text |Cite
|
Sign up to set email alerts
|

Dyspepsia, Helicobacter pylori, and peptic ulcer in a randomly selected population in India.

Abstract: There seems to be a worldwide geographic variation in the prevalence of peptic ulcer disease, although there are few reliable population based studies. This study aimed to determine the prevalence ofpeptic ulcer disease in a community in southern India and to evaluate the relationship between dyspeptic symptoms, Helicobacter pylori infection, gastritis, and peptic ulcer disease. A sample population was selected randomly from a rural monastic settle-.ment in southern India. Subjects were interviewed using a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 24 publications
4
46
2
Order By: Relevance
“…In 2004, other authors reported a prevalence of H. pylori infection in 56% of dyspeptic patients from Karachi [43]; however, in early 2000, Taj et al reported seroprevalence of H. pylori in 80% of the cases from the city [27]. Our report and another from Yakoob et al confirm the decreasing trend of H. pylori infection overtime in Karachi, which is comparable to trends seen in other South Asian and European countries [44][45][46]. Interestingly, earlier studies from northern and central parts of Pakistan reported 66% and 84% prevalence rates among dyspeptic patients [25,29], indicating the difference in H. pylori infection in geographic niches and ethnic groups in Pakistan.…”
Section: Discussionsupporting
confidence: 79%
“…In 2004, other authors reported a prevalence of H. pylori infection in 56% of dyspeptic patients from Karachi [43]; however, in early 2000, Taj et al reported seroprevalence of H. pylori in 80% of the cases from the city [27]. Our report and another from Yakoob et al confirm the decreasing trend of H. pylori infection overtime in Karachi, which is comparable to trends seen in other South Asian and European countries [44][45][46]. Interestingly, earlier studies from northern and central parts of Pakistan reported 66% and 84% prevalence rates among dyspeptic patients [25,29], indicating the difference in H. pylori infection in geographic niches and ethnic groups in Pakistan.…”
Section: Discussionsupporting
confidence: 79%
“…Colonization rates of its human host depend on socioeconomic, ethnic, geographical, and age-related factors [69,70]. Adults from developing countries demonstrate prevalence rates that approach 80% [71,72], while rates less than 60% are seen in industrialized countries [73,74]. In an adult cohort from the United States, positive H. pylori serology ranged from 16.7% for persons 20-29 years old to 56.9% for persons of age 70 or greater, demonstrating a clear age-related prevalence [75].…”
Section: About H Pylorimentioning
confidence: 99%
“…A study from Mizoram reported higher rate of infection by H. pylori in stomach cancer patients (Parkin, 2006). The findings in the study shows a decline of about 20% in the prevalence of H. pylori over last 10years (Graham et al, 1991;Gill et al, 1992;Katelaris et al, 1992;Jain et al, 1999;Misra et al, 2007).…”
Section: Discussionmentioning
confidence: 89%